If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8(m + -5) = 10 Reorder the terms: 8(-5 + m) = 10 (-5 * 8 + m * 8) = 10 (-40 + 8m) = 10 Solving -40 + 8m = 10 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 8m = 10 + 40 Combine like terms: -40 + 40 = 0 0 + 8m = 10 + 40 8m = 10 + 40 Combine like terms: 10 + 40 = 50 8m = 50 Divide each side by '8'. m = 6.25 Simplifying m = 6.25
| m-15=-13 | | -291=3r+5(2+8r) | | r-1=-9 | | X+.5x=21 | | -16t^2+55t+2=0 | | 20(y+1)=8(3y+1) | | (y^1/4)(y^8/3) | | 8x-14=2(4x-9) | | -291=3r+5 | | 6+v=15 | | 18-9y=-3+16y | | 1+k=15 | | 4v+3= | | 46=-4x+7x+10 | | 6b=-6b+3(6+3b) | | (3x/2)-7=(x/2) | | -8x+(-16)=56 | | 3x-2(x-1)=5-x | | T/-2=1/2 | | 4/9x54= | | 88=-8(k-7) | | ln(5)-ln(3)= | | -0.5(10x-6)+4=32 | | 18C-12C=36 | | 9=16y+61 | | p-12=-8 | | 7x+10=23x+20 | | 66=-6x-6(-6x+39) | | 10log^5=x | | k+15=14 | | 7(6m+2)=308 | | 2(7-3x)=(-6) |